Acute effects of the number of players and scoring method on physiological, physical, and technical performance in small-sided soccer games - Manuel Clemente, Filipe (2014)
This study aims to examine the effect of differences in the number of players and scoring method on heart rate responses, time–motion characteristics, and technical/tactical performance during small-sided soccer games. Ten male amateur soccer players (26.4 ± 5.3 years old, 8.4 ± 3.2 years of practice, 179.3 ± 5.2 cm body height, 71.2 ± 7.1 kg body weight, 45.8 ± 2.6 ml.kg–1min–1VO2max) from the Portuguese regional league played nine different small-sided games (i.e., 3 formats × 3 scoring methods). The study used two-way MANOVA, two-away ANOVA, and one-way ANOVA, depending on the specific procedure for the analysis. Compared with other formats, 2v2 induced significantly greater values of technical/tactical indexes (p = 0.001), 3v3 induced significantly higher %HRreserve values (p = 0.001), and 4v4 led to significantly greater distance coverage and speed (p = 0.001). The study provided evidence for coaches to set different small-sided game conditions depending on the training purpose in terms of physiological, physical, and technical performance.